Early detection of meconium peritonitis in term neonate: a case report - Marsubrin, Putri Maharani Tristanita; Iskandar, Stephen Diah; Wulandari, Haryanti Fauzia; Bermanshah, Evita Kariani; Rahayatri, Tri Hening; Roeslani, Rosalina Dewi (Indonesian Pediatric Society, 2025)
Meconium peritonitis (MP) is a very rare, sterile peritonitis that results from fetal gut perforation in utero. Late diagnosis and treatment may cause severe morbidity and mortality related to sepsis. Here we report a term, appropriate for gestational age (AGA) neonate with meconium peritonitis. A one-day-old baby was brought to our hospital with lethargy and progressive abdominal distention for the last 12 hours and hypovolemic shock on admission. The diagnosis of meconium peritonitis was established based on physical examination, supported by abdominal X-ray and ultrasound. A sigmoid colon perforation was found during emergency surgery and a sigmoid colostomy was done. The infant was discharged on the 20th post-operative day with good enteral feeding tolerance.